RESPON TANAMAN BAWANG MERAH (Allium ascalonicum L.) DENGAN PEMBERIAN BEBERAPA DOSIS KOMPOS TANDAN KOSONG KELAPA SAWIT (TKKS) - Yusmalinda, Yusmalinda; Ardian, Ardian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aims to determine the influence of four doses of empty palm bunches compost (EPB) on growth and production of onion (Allium ascalonicum L.) and getting the best doses for the growth and yield of onion. This research has been conducted in the experimental field of the Faculty of Agriculture, University of Riau, Pekanbaru for 2 months starting in February 2016 to April 2016. The research was conducted experimentally using a Completely Randomized Design (CRD) with 5 treatments and  5 replications. The treatments applied in this research was :  0, 5, 10, 15 and 20  tones empty palm bunches compost per ha. Parameters those observed were the plant height, harvesting, the number of tubers per clumps sample, fresh weight of tuber per clumps sample and dry weight of tuber per clumps sample. Data were analyzed statistically by anova and Duncan's test at 5% level. The results showed that implementation of empty palm bunches composts with a dose of 5 tones/ha gave the best results on the plant height, yield, the number of tubers per clumps sample, fresh weight of tuber per clumps sample.  Keyword : onion, Empty Palm Bunches compost, fertilization